Hypoxic mesenchymal stem cell-derived exosomal circDennd2a regulates granulosa cell glycolysis by interacting with LDHA - Wenxin Li; Minjun Lu; Junyu Shang; Jiamin Zhou; Li Lin; Yueqin Liu; Dan Zhao; Xiaolan Zhu (Stem Cell Research & Therapy)
Abstract Background Premature ovarian insufficiency (POI) is an ovarian dysfunction disorder that significantly impacts female fertility. Ovarian granulosa cells (GCs) are crucial somatic components supporting oocyte development that rely on glycolysis for energy production, which is essential for follicular growth. Hypoxia-induced exosomal circRNAs regulate glycolysis, but their biological functions and molecular mechanisms in POI are largely unexplored. The present comprehensive investigation revealed a substantial reduction in ovarian glycolysis levels in POI rats. Notably, hypoxia-induced exosomes originating from mesenchymal stem cells (HM-Exs) exhibit a remarkable capacity to enhance ovarian glycolysis, mitigate GCs apoptosis, reinstate disrupted estrous cycles, modulate sex hormone levels, and curtail the presence of atretic follicles. These restorative actions collectively contribute to fostering fertility revival in POI-afflicted rats. Methods Cyclophosphamide was administered for 2 weeks to induce POI rat model, and POI rats were randomly divided into three groups and treated with PBS, NM-Exs and HM-Exs, respectively. Ovarian function and fertility were assessed at the end of the study and ovarian tissues were collected for analysis of energy metabolites. The relationship between circDennd2a and POI was explored in vitro by qRT-PCR, Western blotting, CCK-8 assay, EdU staining, TUNEL staining, extracellular acidification rate (ECAR) measurements, and ATP, lactate and pyruvate level assays. Results Our findings revealed depletion of circDennd2a in serum samples and GCs from individuals suffering from POI. The introduction of HM-Exs-derived circDennd2a (HM-Exs-circDennd2a) effectively counteracted GCs apoptosis by enhancing glycolytic processes and driving cellular proliferation. CircDennd2a interacted with lactate dehydrogenase A (LDHA), which served as a catalyst to increase LDHA enzymatic activity and facilitate the conversion of NADH to NAD+. This biochemical cascade worked synergistically to sustain glycolytic function within GCs. Conclusion This study revealed that HM-Exs-circDennd2a promoted LDHA activity and enhanced GCs glycolytic capacity, both of which support its use as a potential clinical diagnostic and therapeutic target for POI.